Optimal Distribution of Renewable Energy Systems Considering Aging and Long-Term Weather Effect in Net-Zero Energy Building Design - Lu, Yuehong; Alghassab, Mohammed; Alvarez-Alvarado, Manuel S.; Gündüz, Hasan; Khan, Zafar A.; Imran, Muhammad (Mdpi, 2020)
Generation system interruptions in net-zero energy buildings (NZEBs) may result in missing the net-zero targets by a great margin. Consequently, it is significant to incorporate a realistic reliability model for renewable energy systems (RESs) that considers aging and long-term weather conditions. This study proposed a robust design optimization method that deals with the selection of RES to achieve NZEB. Different case studies were evaluated: 1. Deterministic approach; 2. Markov chain-based reliability without the aging effect; 3. Markov chain-based reliability with the aging effect. The results showed that the optimal sizes of RES, considering the aging effect, were much larger than the other two cases based on the annual energy balance. Moreover, the consideration of the aging effect on the reliability assessment of the generation system for NZEB opens a pathway for a more robust and economic design of RES.
Khan, zafar/0000-0003-3149-6865; Alvarez-Alvarado, Manuel S./0000-0002-0398-9235; GUNDUZ, HASAN/0000-0003-3145-1755; Imran, Muhammad/0000-0002-3057-1301
Keywords: aging effect; Markov chain model; Monte Carlo simulation; net-zero energy building